NEWLY DIAGNOSED STROKE-ASSOCIATED ATRIAL FIBRILLATION: RISK OF DEVELOPMENT OF UNFAVORABLE CLINICAL OUTCOMES (THE RESULTS OF THE SUBANALYSIS COHORT STUDY APOLLO) - I. A. Zolotovskaya; I. L. Davydkin; D. V. Duplyakov (Архивъ внутренней медицины, 2017)
Objective: to study the prognosis of patients with first diagnosed atrial fibrillation in patients after cardioembolic stroke. Material and methods. In an open, prospective study “APOLLO” (Anticoagulation in Patients with atrial fibrillation, after cardioembolic stroke) for the period 01.10.2013 — 31.03.2015 after the stage of screening (n=1291) were included 661 patients with atrial fibrillation, after cardioembolic stroke, the average age was 68,0 [62,0; and 74,0] years. The observation period is 12 months. Results. Noted the high level of comorbidity (hypertension was verified in 100% of patients, ischemic heart disease — 61,4% of patients, diabetes in — 52,3%, and chronic kidney disease have to 32.1% of patients). At 154 (23,3%) patients AF was first diagnosed at the time of the development of cardioembolic stroke. Patients with first diagnosed atrial fibrillation were comparable with the whole group in age, indicator of the scale HAS-BLED, the frequency of occurrence of hypertension, but among them were significantly more frequently encountered patients with chronic kidney disease, diabetes, and myocardial infarction. The greatest mortality during the year was observed in the group of patients with first diagnosed atrial fibrillation, where he died — 46 (29.9 per cent) of people that is significantly more than the average across the group of patients with atrial fibrillation, after cardioembolic stroke, and patients with different forms of atrial fibrillation (p<0.001). Deceased patients with first diagnosed atrial fibrillation were significantly older and had a more pronounced degree of neurological deficit by NIHSS scale. Conclusion. The data obtained showed high prevalence and poor prognosis newly diagnosed with atrial fibrillation in patients with cardioembolic stroke. The use of the term “newly diagnosed stroke-associated atrial fibrillation” logically justified, which determines how the time of onset of this arrhythmia and high risk of mortality in patients of this group.